(untitled) (IMC Journal of Medical Science, 2018)
Background and objectives: Vaginoplasty is a procedure for the reconstruction of vaginal canal. Various surgical techniques have been described for vaginal reconstruction with variable success. The aim of this study was to assess the use of sigmoid colon in vaginal reconstruction of patients with disorders of sex development. Methods: Eleven patients were included in this study from January 2009 to December 2016. All patients underwent karyotyping, pelvi-abdominal ultrasonography, endocrine and psychiatric assessment. Sigmoid neo-vaginoplasty was the procedure chosen for all the cases. Surgical and functional outcomes were assessed post-operatively over a period of 6 month to 6 years. Results: The preoperative diagnosis included 9 cases of aplasia of the Mullerian ducts or Mayer-Rokitansky-Küster-Hauser syndrome (MRKH), 1 androgen insensitivity syndrome (AIS) and 1 pseudohermaphrodite case. The mean age of the study population was 22.5 years (range 15-30 yrs). No intra-operative or early postoperative complications occurred. The mean vaginal length achieved was 13.0 cm (range 10.5 – 15 cm). Long term follow-up showed introital stenosis in 2 cases (17%) which resolved well to vaginal dilatation. One patient had pelvic abscess and treated by surgery. Sexual satisfaction was achieved in 10 cases, as 1 case was unmarried. Conclusion: For patients with disorders of sex development of various etiologies, sigmoid vaginoplasty is the preferred technique for vaginal reconstruction. It is a safe technique and provides the patient with a cosmetic neovagina of adequate caliber with satisfactory functional outcome. IMC J Med Sci 2018; 12(1): 27-31